2019 Roger A. Mann Award Winner: Imaging of Bone Perfusion and Metabolism in Subjects Undergoing Total Ankle Arthroplasty Using 18F-Positron Emission Tomography. Issue 4 (16th October 2019) - Garfinkel, Jonathan H.; Dyke, Jonathan P.; Volpert, Lauren; Sanders, Austin; Newcomer, Meghan; Sofka, Carolyn M.; Ellis, Scott J.; Demetracopoulos, Constantine A.
Category: Ankle Arthritis Introduction/Purpose: Total ankle replacement (TAR) continues to exhibit a relatively high incidence of complications and need for revision surgery, particularly when compared to knee and hip arthroplasty. One common mode of failure in TAR is talar component subsidence. This may be caused by disruption in the talar blood supply related to the surgical technique. Positron emission tomography (PET) imaging with [18F]-Fluoride has demonstrated utility in evaluating bone perfusion, and PET-CT in particular is useful in the setting of total joint replacement. In this study we aim to quantify changes in talar perfusion before and after TAR with the INBONE II system (Wright Medical Technology, Inc., Memphis, TN) using [18F]-Fluoride PET-CT. It is our hypothesis that perfusion to the talus would decrease after TAR. Methods: Eight subjects (5M/3F) aged 70.4 ± 7.5 years [Range 61-83] were enrolled for 18F-PET/CT imaging prior to and 3 months following TAR. 5–10 mCi of 18F-Fluoride was administered and dynamic acquisition in list mode for 45 minutes was performed on the operative and non-operative ankles simultaneously on a Siemens mCT Biograph scanner. Static acquisition of the whole body was also performed one hour after injection. Regions of interest (ROI's) were placed on the postoperative CT images in the body of the talus beneath the INBONE II talar component. These regions were manually delineated on the preoperative CT scans, and were drawn to replicate the ROIs placed on the postoperative studies. ROI's were overlaid on the fused static 18F-PET images and standard uptake values (SUVs) calculated for these regions as well as the whole foot. Changes in SUVs were analyzed using a paired t-tests with a significance level of 0.05. Results: We found no significant difference in bone perfusion in the talus after TAR in our cohort of patients. 18F uptake in the ROI underneath the talar component compared to that measured at baseline prior to surgery was 3.36 +/- 1.44 SUV postoperatively vs. 2.65 ± 1.24 SUV preoperatively, (p=0.33). Similar results were seen in the whole foot: 2.99 +/- 1.22 SUV postoperatively vs. 2.47 ± 0.75 SUV preoperatively (p=0.16). Figure 1 displays preoperative and postoperative uptake in the bone in the area corresponding to the base of the talar component. Although we did not find a significant difference in our initial study, the observed increase in perfusion to the talus after TAR may reach significance with a larger cohort of patients. Conclusion: 18F-PET demonstrates the ability to quantify changes in bone perfusion and metabolism following TAR. Our results suggest that the vascular blood supply to the talus is not disrupted after TAR. Additional pharmacokinetic analysis of the dynamic activity curves will also allow for estimates of bone blood flow and osteoblastic turnover via compartmental modeling. These results may be used to confirm the presence of adequate bone blood flow and vascularity in the body of the talus following total ankle replacement.